LOVE AND FIDELITY: A FEMINIST STUDY ON RAMA-SHINTA STORY IN THE NOVEL KITAB OMONG KOSONG BY SENO GUMIRA AJIDARMA - Nirmalawati, Widya; Wahyuningsih, Titik (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2017)
Rama-Sintha is a very legendary story, however this story is always worth-watching in various forms—film, dancing, drama, novel even in cartoon. Seno Gumira Ajidarma, is one of the writers who retells the story from different point of view. Kitab Omong Kosong, referred to as KOK, tells about Sintha's lawsuit against Rama's love. The novel no longer tells about the epic of their legendary love story, but it criticizes love and virginity-orientation in a patriarchal culture. This is due to the reason what Shinta has experienced in KOK, representing the imbalance of woman in society. This research will use content analysis to reveal the KOK using feminist’s perspectives. This study will employ a feminist point of view to see a biased association of love to virginity. In patriarchal culture, virginity becomes one of the standards to value one’s love. The result of this research shows that KOK,is a deconstruction of Rama-Shinta love story, to a story full of anger, arrogance, and jealousy. As lelanang (man), Shinta is a symbol of power. Her kidnapping by Rahwana is a humiliation against Rama’s dignity. Thus, to receive her back as his wife, Rama asked her to prove her purity and loyalty. This is shows unequal power between Rama and Shinta, as two lovers. She was a true victim of patriarchy. Her choice to disappear (moksa) is a resistance struggle against his beloved husband’s domination. DOWNLOAD ABSTRACT